Evaluation of tyrosinase inhibitory activity in Salak (Salacca zalacca) extracts using the digital image-based colorimetric method - Nuntaporn Moonrungsee (2018)
© 2018, Institute of Chemistry, Slovak Academy of Sciences. A simple toolbox was developed for the evaluation of tyrosinase inhibitory activity in Salak (Salacca zalacca) extracts by the colorimetric measurement based on a photograph taken by a digital camera or a smartphone camera. The reaction of 3,4-dihydroxyphenylalanine (l-DOPA) and tyrosinase was employed to form the dopaquinone dye, which decreases with the increase of the tyrosinase inhibitor. Under the optimum conditions, the Salak extracts were examined for the tyrosinase inhibitory activity. The captured picture of dopaquinone dye product was analyzed by reading blue color intensity using an Adobe Photoshop CS6 program. The tyrosinase inhibition of the extracts was calculated from the blue color intensity, and expressed as %inhibition and IC50values. The obtained results from the developed method correlated well with those obtained from the microplate reader instrument. The achievement of this research will be a guideline for creating any simple analytical instrument based on colorimetry. In addition, the information on tyrosinase inhibitory activity of the Salak extracts is useful for the application of this fruit to produce the supplement food and the cosmetic in the future.